Muscularity and Strength Affect Individual Variation in Self-Perception of Fighting Ability in Men - Muñoz-Reyes, José Antonio; Polo, Pablo; Rodríguez-Sickert, Carlos; Pavez, Paula; Valenzuela, Nohelia; Ramírez-Herrera, Oriana (Frontiers in Psychology, 2019)
Objective: There is evidence that competitive conflicts are the main form of intrasexual competition among men. The capacity to recognize visual cues of fighting ability in competitors is thought to be an important characteristic that allows men to avoid the costs of contest competition. However, for an accurate comparison to take place, individuals need to compare the fighting ability of their competitors to their own to assess this asymmetry. Methods: In order to improve our understanding of this self-assessment process, here we study the relationship between visual fighting ability cues, namely i) muscularity, as measured with a bioimpedance device, ii) the real capacity to inflict cost to a rival based on strength, as measured with a hand grip dynamometer (HGS), and iii) self-perceived fighting ability, as determined with a questionnaire. The study sample was 364 men between 18 and 38 years of age (M ± SD = 22.27 ± 3.99). Results: Our results confirm the expected positive relationship between upper-body muscularity and strength, while controlling for Body Mass Index (BMI). However, muscularity explained only around 30.2% of the variance in strength. In addition, muscularity was related to self-perception of fighting ability in our sample, its effect being partially mediated by strength. Conclusions: The ore muscular men perceive their fighting ability as being greater, and not only because they are stronger (at least in the HGS task). Accordingly, it seems that men take into account the overestimation the robustness of the relationship between strength and muscularity that prevails within his peers.